Global Health Governance: Conflicts on Global Social Rights - Wolfgang Hein; Lars Kohlmorgen (German Institute of Global and Area Studies (GIGA), 2005)
This paper analyses the impact of new institutional structures in global health governance on the realization of social rights in poor countries. Meanwhile, health is broadly seen as an import precondition for social and economic development. This leads to an integration of the "diseases of the poor" (basically infectious diseases) into strategies of fighting poverty. Considering the example of global HIV/AIDS politics, the paper argues that new governance modes increase the participation of civil society groups and affected communities, but that they are also frequently instrumentalised by powerful actors to pursue their particular interests. In fact, increasing resources are mobilized for the fight against poverty related diseases. The paper concludes that global health governance is characterized by a combination of moral values and material interests which does not guarantee a comprehensive realization of social rights, but which allows some progress in the fight against poverty-related diseases – a precondition of the possible further realization of social rights.
Keywords: 300; Global Health Governance; New Governance Modes; International Organizations; Social Rights; Global Social Justice; Developing Countries; HIV/AIDS Politics; Global Governance; Gesundheit; Gesundheitsversorgung; TRIPS; Menschenrechte; Welt